Effect of rheological additives on rheological properties of fly Ash-based sealing coatings. (4th April 2022) - Song, Huiping; Wang, Xiaoqian; Xie, Wensheng; Di, Zichen; Cheng, Fangqin
Abstract: Gas emissions in coal mines seriously threaten the safety of mines. Sealing coatings are an effective method to relieve gas emissions. During the curing process of fly ash-based sealing coatings, a large number of inorganic particles, such as fly ash are prone to particle sedimentation, which leads to obvious delamination of the coating and affects its performance. In this paper, fumed silica (AEROSILR974), polyurethane thickener (BYK-6500) and polyurea thickener (BYK-420) were selected as the rheological additives of water-based coatings to improve the viscosity of the system, which would improve the coating delamination caused by the sedimentation of inorganic particles. The effects of different rheological additives on the anti-sagging and thickening effects of the system were studied using static mechanical tests including shear rate-viscosity and power law correlation. The results showed that 0.22% BYK-420 was dispersed in the coating system to form a stable and good three-dimensional network, and had the yield force of more than 10 Pa, high thickening efficiency and obvious shear thinning characteristics. The system showed better solid behavior and thixotropy, which could prevent sedimentation and sagging. Meanwhile, adding rheological agent BYK-420 was beneficial to curing the coating, which has practical significance for improving the compactness of the coating.